An alternative and more cost effective method of delivery of radiotherapy in age related macular degeneration. Issue 4 (1st April 1998) - Churchill, Amanda J; Franks, Wendy A; Ash, Dan V
Abstract : AIMS/BACKGROUND: In the past 5 years there has been a dramatic increase in the use of radiotherapy to treat subfoveal neovascular membranes (NVMs) in both Europe and the USA despite the high cost. An alternative, more cost effective method of delivery using x ray simulation and bite block head fixation is described. METHOD: 15 patients were recruited with classic subfoveal NVMs. Head fixation was achieved with a customised Perspex mask for eight patients and a bite block for seven. An x ray simulator was used to check the field of irradiation. No computerised tomography (CT) was performed. All patients received a total dose of 13.3 Gy ionising radiation. Visual acuities were charted before and after treatment over a 24 month period. RESULTS: After 24 months, 5/8 (67%) in the mask group showed stable visual acuities (less than two line change on Snellen chart) compared with 3/7 (43%) in the bite block group. This difference may be attributed to a variation in the pretreatment visual acuities in the two groups. From several studies it has been estimated that 24 months after diagnosis 28% untreated individuals would have stable vision compared with 53% patients in this study. CONCLUSIONS: These results compare favourably with other studies and show that teletherapy can be a safe and effective form of treatment for subfoveal NVMs. The authors have described an alternative method of head fixation and shown that CT scanning is not essential. This method of delivery is considerably less costly than that traditionally used and may allow greater numbers of patients to benefit from radiotherapy treatment.